Trade and jobs: a description of Swedish labor market dynamics - Hildegunn Kyvik Nordås; Magnus Lodefalk; Aili Tang (Örebro University School of Business, 2019)
We perform a granular analysis of Swedish labor market dynamics, using matched employer employee and firm level trade data for Sweden over a 15-year period. The employment share in firms that are directly exposed to international trade has decreased, due to a shift in employment towards personal and public services. Analyzing the dynamics, we find that workers in firms that change export status are slightly less likely to obtain the same wage rise as their peers. However, workers that stay in the same job in trading firms are less affected by changes in export and offshoring volumes, with the exception of high-skilled workers in manufacturing firms who face a downward pressure on wages from services offshoring, but higher wages from services exports. Finally, we find that exports and offshoring of goods and services stimulate labor demand. While exports and offshoring of services increase relative demand for skilled workers, exports and offshoring of goods stimulate relative demand for middle and low skilled workers.
Keywords: E24; F16; F66; J63; P23; 330; Worker flows; Job flows; Trade; Wages; Labor Demand